Artist residency in the classroom: a possible experience? (Revista Apotheke, 2024)
This article intends to reflect on the lessons learned from an Extension Project entitled “Artist Residency” - proposed by a professor of an undergraduate curricular subject, at the Institute of Humanities, at Unilab (Universidade da Integração Internacional da Lusofonia Afro-brasileira) – based on the experience of one of the invited artists from the work “Livro-mobiliário, um livro de artista” and his creation processes. Thus, its objectives are: move some places and concepts concerning the field of arts and its performances; reflect on curricular subjects as spaces that are established as processes of knowledge with the human aspect; understand about a plastic experimentation of artist residency; and to present a practice of expanding perception and coexistence between academic and non-academic communities, with artistic languages. To this end, it experimented with diversified methodologies in the form of critical debates, didactic-artistic exercises, textual productions and elaborations of works of art presented at the end of the semester by students and invited artists. The “Artist Residency”, in this perspective, in addition to being an innovative proposal, sought to contribute to the understanding of teaching-learning process in the Brazilian public university as a place of exchange and mutual sharing of knowledge. The main theoretical contributions for this text were: BASBAUM (2013), BARTHES (2003), CARRIÓN (2011), DERDYK (2013).
Keywords: artist residency; artist’s book; teaching-learning; creation processes